Canonical nonequilibrium statistics and applications to Fermi-Bose systems - Ebeling, W. (Condensed Matter Physics, 2000)
The aim of this work is the study of a special class of nonequilibrium systems which admits to ﬁnd exact stationary solutions of the kinetic equations. In particular we investigate canonical-dissipative systems, where the driving terms are determined by the Hamiltonian or other invariants of motion only. We construct systems which drive the system to special invariants of motion and solve the corresponding Fokker-Planck equations. Finally several applications to mean-ﬁeld problems for fermion and for boson systems are discussed.